BK Virus Nephropathy and Transplant Outcomes: A Single Center Study - Ojha, Prashanta; Singh Shah, Dibya; Phuyal, Mandira; Mishra, Anand; Sigdel, Mahesh Raj (Journal of Institute of Medicine Nepal, 2024)
Background: A significant proportion of renal allografts are complicated by BK Polyoma Virus infection which, if not managed in time, leads to BK Polyoma virus Nephropathy (BKVN). Early recognition and reduction of immunosuppressants is the mainstay of management of BKVN. We aimed to study the clinical characteristics of patients with BKVN, its timeline, management strategies and its outcome at one year of diagnosis. Methods: An observational study was done in Tribhuvan University Teaching Hospital, Nepal, in September 2024. The medical records of living-donor renal transplant recipients between August 2008 to April 2024 with biopsy proven BK virus Nephropathy were reviewed. Time since transplant, recipient age, recipient sex, donor age, donor sex, relationship with Donor, Blood group compatibility, induction agent and immunosuppressive used at the time of BKVN diagnosis, mode of diagnosis and clinical presentation, co-morbid diabetes, other infections during the time of diagnosis, changes in maintenance immunosuppression, other treatments received, renal function 1 year after diagnosis and need for dialysis were studied. Results: Out of 847 living-donor kidney transplants, 15 (1.77%) had BK virus nephropathy. Thirteen (86.7%) were males; mean age was 42 ± 11.53 years and 5(were diabetic. Average HLA mismatch was 3/6. BKVN was diagnosed after a mean period of 16.07±13.24 months after transplant. Thymoglobulin was used as induction agent in 11(73.3%) cases. All the patients were on Tacrolimus, Mycophenolate mofetil and Prednisolone. Average creatinine was 147.93±40.882µMol/L. Patients were managed with reduction in immunosuppressives and fluoroquinolones. Average creatinine after 1 year of diagnosis was increased by 10% to 164.43 ± 101.03µMol/L while one patient required maintenance hemodialysis 3 years later. Conclusion: BKVN was seen in less than 2% of renal allograft recipients; at 16.07±13.24 months after transplant. There was significant renal dysfunction at diagnosis which did not improve at one year, while 1 patient required maintenance hemodialysis.